Urinary Tract Infections Caused by Klebsiella pneumoniae and Prolonged Treatment with Trimethoprim/Sulfamethoxazole - Rumen Filev; Mila Lyubomirova; Boris Bogov; Alexander Kolevski; Victoria Pencheva; Krasimir Kalinov; Lionel Rostaing (Microorganisms, 2025)
Urinary tract infections (UTIs) are among the most prevalent bacterial infections, with Klebsiella pneumoniae emerging as a significant multidrug-resistant pathogen, particularly in healthcare settings. The frequent utilization of β-lactams and fluoroquinolones has contributed to the reduced clinical application of trimethoprim-sulfamethoxazole (TRS). Nevertheless, this reduced use may have preserved its efficacy as a second-line therapy. The aim of this study is to determine whether TRS can be a cost-effective long-term solution for patients with multidrug-resistant K. pneumoniae UTIs. This study evaluated the effectiveness of a structured, long-term TRS regimen in 11 patients with recurrent K. pneumoniae UTIs who had failed at least two prior antibiotic treatments. Patients were carefully selected, and the collected data were analyzed using descriptive analysis. The findings demonstrated microbiological eradication and symptomatic relief in all patients, with only one case of a delayed allergic reaction. All patients had a negative urine microbiology analysis after at least two unsuccessful treatment attempts over a period of 6 to 18 months. These results underscore TRS’s potential as a cost-effective and efficient second-line treatment, particularly in settings with limited therapeutic options. Its affordability, manageable side effect profile, and ability to target biofilm-associated infections further highlight its therapeutic value.